Microevolution of cis-regulatory elements: an example from the pair-rule segmentation gene fushi tarazu in the Drosophila melanogaster subgroup. - Mohammed Bakkali (PLoS ONE)
The importance of non-coding DNAs that control transcription is ever noticeable, but the characterization and analysis of the evolution of such DNAs presents challenges not found in the analysis of coding sequences. In this study of the cis-regulatory elements of the pair rule segmentation gene fushi tarazu (ftz) I report the DNA sequences of ftz's zebra element (promoter) and a region containing the proximal enhancer from a total of 45 fly lines belonging to several populations of the species Drosophila melanogaster, D. simulans, D. sechellia, D. mauritiana, D. yakuba, D. teissieri, D. orena and D. erecta. Both elements evolve at slower rate than ftz synonymous sites, thus reflecting their functional importance. The promoter evolves more slowly than the average for ftz's coding sequence while, on average, the enhancer evolves more rapidly, suggesting more functional constraint and effective purifying selection on the former. Comparative analysis of the number and nature of base substitutions failed to detect significant evidence for positive/adaptive selection in transcription-factor-binding sites. These seem to evolve at similar rates to regions not known to bind transcription factors. Although this result reflects the evolutionary flexibility of the transcription factor binding sites, it also suggests a complex and still not completely understood nature of even the characterized cis-regulatory sequences. The latter seem to contain more functional parts than those currently identified, some of which probably transcription factor binding. This study illustrates ways in which functional assignments of sequences within cis-acting sequences can be used in the search for adaptive evolution, but also highlights difficulties in how such functional assignment and analysis can be carried out.